Performance of foreign banks in developing countries: Evidence from sub-Saharan African banking markets - Pelletier, Adeline (Journal of Banking & Finance, 2018)
Do foreign banks perform better than domestic banks in host developing economies? Relying on financial statements and survey data I compare the performance of three different categories of foreign banks to the group of domestic banks in sub-Saharan Africa: global banks from developed countries, regional African banks and banks from non-African emerging economies. While emerging-market banks and global banks consistently outperform domestic banks, the difference is not significant for regional African banks. The higher performance of global banks and emerging-market banks is related to higher operational efficiency and lower cost of funding, while there is no strong evidence of segmentation by business segment in the loans market. Regional African banks, which started their foreign expansion more recently, are less able to generate interest income compared to domestic banks. These findings highlight the importance of taking into account foreign banks’ heterogeneity when assessing the impact of financial FDI on the host economy.